The Role of the Byzantine Navy in the Actions of Emperor Louis II of Italy against Bari in 866–871. Louis II’s Letter of 871 to Emperor Basil I (867–886) – as a Source for Marine Military Studies? - Böhm, Marcin (Studia Ceranea, 2023)
The rivalry between the Carolingians and the Byzantines in Italy during the second half of the 9th century faced a new threat – the rise of Islam. Despite the need to unite against the common enemy, mutual suspicion between these two centres of imperial power persisted. This is evident in their joint efforts to confront the Muslim outpost in Apulia, the Emirate of Bari. This article aims to examine the role of the Byzantine fleet in the actions of Emperor Louis II (825–875) during the campaign to eliminate the Emirate of Bari – a task in which the Carolingian ruler was successful. The primary source for this investigation is Louis II’s letter of 871 to Emperor Basil I (867–886). In the letter, the author identifies the links between the activities of Muslims in the Adriatic and Tyrrhenian Seas and their strongholds in Sicily and Africa. Consequently, the author outlines a logical plan to expel the Saracens from Italy, particularly from Campania (Naples) and Calabria, with a crucial role assigned to the Byzantine fleet. The Franks intended to coordinate land operations with the Byzantines in Sicily, aiming to reclaim Palermo – a city, according to the letter, closely linked to the Muslim piracy. However, this plan was based on wishful thinking, as it failed to consider the dispersion of the Byzantine navy, which was simultaneously engaged in conflicts against the forces of the Abbasids, the emirate of Crete, and the Slavic pirates in the Adriatic Sea. These factors, coupled with a growing aversion between the Franks and the Byzantines, ultimately led to the collapse of the alliance and their plans. Despite later successes, the Byzantine fleet was unable to provide timely aid to Sicily and actively counter the advance of Islam on the island.